Impedance study on Mg Sacrificial anode for soil corrosion protection - Zulkifli Zainon (Universiti Malaysia Perlis, 2008)
Sacrificial anode is one of the methods that usually applied in soil corrosion protection especially magnesium (Mg) based anode. This study is focuses on high-potential Mg anode and pure Mg anode. The value of open-circuit potential for as-received high-potential Mg anode, as-cast high-potential Mg anode and pure Mg anode are -1679, -1546 and -1709 mV vs SCE respectively. The corrosion rate and corrosion current density exhibits the significantly different between Mg anodes. The highest corrosion rate and corrosion current density was achieved by as-cast high-potential Mg anode (25.7754 µm/year, 1.02 A/cm2), followed by as-received high-potential Mg anode (4.1476 µm/year, 0.158 A/cm2) and pure Mg anode (2.3985 µm/year, 0.105 A/cm2) respectively. The different of the electrochemical properties were believed resulted by the presence of alloying element and different process among the samples. Electrochemical impedance spectroscopy study shows the large resistance resulted by high passive properties of as-cast high-potential Mg anode. This occurrence is at high solution and polarization resistance condition due to the existence of passive layer on sample surface. The presence of oxide passive layer results the flow of electron was prevented. A heterogeneous structure of surface layer on as-received high-potential Mg anode shows resistance properties in small value with low passivity thus increased the electron flow and transfer on it surface.